Hubungan antara kemampuan numerik, kemandirian belajar, dan hasil belajar matematika siswa kelas V sekolah dasar se gugus baturaden kecamatan grogol - Saa'dah, Aprilia Lailatus; Riyadi, Riyadi; Atmaja, Idam Ragil Widianto (Didaktika Dwija Indria, 2026)
The aim of this research is to find out the relationship between numerical ability and self-regulated learning with mathematics learning outcomes of 5th grade students of SDN Gugus Baturaden, Grogol District. There are 3 variables in this research, namely numerical ability (X1), self-regulated learning (X2) as independent variables, and learning outcomes (Y) as dependent variables with a type of quantitative research with correlation approach. The samples in this study was 42 students. Data on numerical skills and learning outcomes were obtained through test instruments and data on self-regulated learning were obtained through questionnaire instruments. Descriptive quantitative data analysis using both basic and multiple correlation analysis is the method employed. The results of the analysis show that 1) there is a relationship between numerical ability and mathematics learning outcomes, 2) there is a relationship between self-regulated learning and mathematics learning outcomes, and 3) there is a relationship between numerical ability, self-regulated learning and mathematics learning outcomes. Consequently, it can be said that the mathematics learning results of fifth-grade elementary students in Gugus Baturaden, Kecamatan Grogol, are correlated with both numerical aptitude and self-regulated learning.